Prevalence of Poor Sleep Quality in Perinatal and Postnatal Women: A Comprehensive Meta-Analysis of Observational Studies - Yang, Yuan; Li, Wen; Ma, Tian-Jiao; Zhang, Ling; Hall, Brian J.; Ungvari, Gabor S.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2020)
Background: Sleep disturbance is common in perinatal and postnatal women, but the epidemiology of sleep problems is highly variable in these populations. This is a meta-analysis to examine the prevalence of poor sleep quality and its correlates among perinatal and postnatal women. Methods: A systematic search of both international and Chinese databases (PubMed, EMBASE, PsycINFO, Web of science, CNKI, and Wangfang) was performed. Studies with data on sleep quality measured by the Pittsburgh sleep quality index (PSQI) were included. Results: Forty-two studies were included for analyses. The prevalence of poor sleep quality was 54.2% (95% CI: 47.9-60.5%) in perinatal and postnatal women, with 44.5% (95% CI: 37.6-51.6%) in perinatal women and 67.2% (95% CI: 57.6-75.5%) in postnatal women. The pooled total PSQI score was 7.54±0.40 (95% CI: 6.75-8.33), while the average PSQI component scores varied from 0.13±0.04 for use of sleeping medication to 1.51±0.17 for habitual sleep efficiency. Maternal age, study location/site, survey year, comorbidity, and PSQI cut-off value had significant moderating effects on the prevalence of poor sleep quality. Conclusion: Given the negative impact of poor sleep quality on health outcomes and wellbeing, regular screening for poor sleep quality and effective interventions should be conducted for this population.